Brief Report: Association of Myositis Autoantibodies, Clinical Features, and Environmental Exposures at Illness Onset With Disease Course in Juvenile Myositis. Issue 3 (March 2016) - Habers, G. Esther A.; Huber, Adam M.; Mamyrova, Gulnara; Targoff, Ira N.; O'Hanlon, Terrance P.; Adams, Sharon; Pandey, Janardan P.; Boonacker, Chantal; van Brussel, Marco; Miller, Frederick W.; van Royen‐Kerkhof, Annet; Rider, Lisa G.; et al.
Abstract : Objective: To identify early factors associated with disease course in patients with juvenile idiopathic inflammatory myopathies (IIMs). Methods: Univariable and multivariable multinomial logistic regression analyses were performed in a large juvenile IIM registry (n = 365) and included demographic characteristics, early clinical features, serum muscle enzyme levels, myositis autoantibodies, environmental exposures, and immunogenetic polymorphisms. Results: Multivariable associations with chronic or polycyclic courses compared to a monocyclic course included myositis‐specific autoantibodies (multinomial odds ratio [OR] 4.2 and 2.8, respectively), myositis‐associated autoantibodies (multinomial OR 4.8 and 3.5), and a documented infection within 6 months of illness onset (multinomial OR 2.5 and 4.7). A higher overall clinical symptom score at diagnosis was associated with chronic or monocyclic courses compared to a polycyclic course. Furthermore, severe illness onset was associated with a chronic course compared to monocyclic or polycyclic courses (multinomial OR 2.1 and 2.6, respectively), while anti‐p155/140 autoantibodies were associated with chronic or polycyclic courses compared to a monocyclic course (multinomial OR 3.9 and 2.3, respectively). Additional univariable associations of a chronic course compared to a monocyclic course included photosensitivity, V‐sign or shawl sign rashes, and cuticular overgrowth (OR 2.2–3.2). The mean ultraviolet index and highest ultraviolet index in the month before diagnosis were associated with a chronic course compared to a polycyclic course in boys (OR 1.5 and 1.3), while residing in the Northwest was less frequently associated with a chronic course (OR 0.2). Conclusion: Our findings indicate that myositis autoantibodies, in particular anti‐p155/140, and a number of early clinical features and environmental exposures are associated with a chronic course in patients with juvenile IIM. These findings suggest that early factors, which are associated with poorer outcomes in juvenile IIM, can be identified.